Paulo Freire e Bakhtin: um diálogo possível - Moura, Edite Marques de (2011)
This thesis is a study of Freire´s approach on literacy, from the hypothesis of interface between his pre- ssumptions and bakhtinians about philosophy of language, traced in our objective. For that, the books that Freire read, in order to organize his proposals were reread. In this sense, SOUZA's (2001) sketch was essential, with the book Um convite à leitura de Paulo Freire. When reading Freire's trajectory, some studies are vital: Vasconcelos e Brito (2006), um glossário dos Conceitos de educação em Paulo Freire, dealing with terms like antidialogicity, dialogue, dialogicity, dialogism. Rosas (2004) and Scocuglia (1999), intends to seize the experiences that led to the books which fundamented the conceptions in "tempos fundantes". In this perspective, the path of bakhtinian philosophical concepts was maped, chronologically, according to biographers as Clark and Holquist (2003), Ponzio (2008). In treating the main concepts of Bakhtin, studies were taken on Brait (2005, 2006 and 2009) and others like Faraco and Tezza (2009); Faraco (2001), Tezza (2002); SOUZA (2002), Fiorin (2001), SOBRAL (2005, 2009), that point out that path of the main concepts which constitute his philosophy, such as language, word, consciousness, dialogue and dialogism. Not in a static perspective, but in the philosophical macro-project of this thinker that put the language in the centre of human interaction, from which results in valuing the world, reflected and refracted for words, the language tool. That project apparently came from the same place that Freire´s did, who created an educational approach, in which words could stop serving oppression. During that process, Freire systemized propositions for literacy, which, in this study, were named Pedagogy of Reading. The analisis of Bakhtin´s thought came from the text Para uma filosofia do ato, spotlighted as the philosophical matrix of everything that comes later; which confirms and explains the other texts (Amorin, 2009) ; "synthesis of bakhtinian thought" (SOBRAL, 2005). By Freire, it iniciates by A Importância do Ato de Ler, in the three articles that complete each other (2008), which demands the appreciation of the first study of Freire´s thought: Educação e Atualidade Brasileira (2001), passing by others , in which he builds his approach for reading. In a brief discussion, the motivating historical-sociological aspects for bakhtinian philosophy, the concepts sketched in the basis of his philosophical anthropology. By Freire, in the third chapter, there are philosophical-linguistic preassumptions for reading. In the next chapter, two ways: the analysis of Freire and bakhtinian paths space and time, implicit or explicit conceptions in their texts, divergences and convergences between their bibliographical influence. Then, a comparison of what is called, in this thesis, Freire´s Pedagogy of Reading and the bakhtinian philosophy of language, their theoretical lines. Approximation and-or distances between their conceptions of language, word, consciousness, dialog and dialogism, in the books they read. In conclusion, we present the (mis)matches between these two masters of Dialetic.